2021
DOI: 10.1101/2021.06.22.21259341
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Similar costs and outcomes for differentiated service delivery models for HIV treatment in Uganda

Abstract: Background: Like many countries in sub-Saharan Africa, Uganda has scaled up differentiated service delivery models (DSDMs) for HIV treatment, but little information is available about the relative costs of the models. We estimated the total annual cost per patient and total cost per patient virally suppressed in five DSDMs, including facility- and community-based models and the standard of care. Methods: We conducted a cost/outcome study from the perspective of the service provider, using retrospective patien… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…All were sponsored by the U.S. Agency for International Development and the U.S. President's Emergency Program for AIDS Relief (PEPFAR) under the EQUIP Health project. Clinical outcomes and costs of these studies have previously been reported [5][6][7][8][9][10][11] . All utilized primary healthcare clinics and/or hospital outpatient clinics to implement and evaluate between three and six differentiated models of delivery of antiretroviral therapy for stable, adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…All were sponsored by the U.S. Agency for International Development and the U.S. President's Emergency Program for AIDS Relief (PEPFAR) under the EQUIP Health project. Clinical outcomes and costs of these studies have previously been reported [5][6][7][8][9][10][11] . All utilized primary healthcare clinics and/or hospital outpatient clinics to implement and evaluate between three and six differentiated models of delivery of antiretroviral therapy for stable, adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to support these assumptions is accumulating but remains scarce. A few DSD programs have been formally described and evaluated in the literature (2)(3)(4)(5)(6)(7)(8)(9)(10)(11); many others are being implemented officially or as pilot projects under routine care, without formal evaluation. Models that have been rigorously evaluated have often been implemented in the course of randomized trials, rather than routine practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…The INTERVAL trial, a cluster-randomized, non-inferiority trial conducted in Malawi and Zambia, found that 6-month ART dispensing was non-inferior in terms of 12-month retention, compared to standard of care [8]. DSD models have consistently been found to save substantial time and money for patients themselves, and satisfaction with the models among both providers and patients has been high [810].…”
Section: Introductionmentioning
confidence: 99%